New design of a two stroke modular engine for multipurpose usage with lean burn capability - Bakar, R. A. (2008)
Significant growth in compression ignition (CI) engine usage was seen in European countries and will spread globally. The ability to burn more efficiently while producing low levels of emission, especially C02 gas emission has increased CI engine's popularity against the spark ignition engines. A new low speed CI engine was designed for agricultural application. A two-stroke working cycle was chosen as it provides very attractive characteristics for its application. The important contribution to the new design is the ability for the engine to generate high tumble incylinder airflow. Higher in-cylinder air movement is favorable for a better and controlled combustion. Consequently, brand new scavenging method driven two stroke engine based on modularity concept was proposed in the project. For virtualization and flow analysis, computational fluid dynamics simulation methodology was used to investigate the proposed in-cylinder airflow. Unidirectional exhaust airflow was detected at the beginning of the exhaust opening period. Further improvement of the combustion in this design would be having fresh air introduce into the cylinder without interrupting the unidirectional exhaust airflow. Judging by the path of the in-cylinder air flow, during the closure of exhaust port, the momentum of the in-cylinder airflow would be converted into tumble flow during the compression stroke. A high tumble flow characteristic in the engine will be obtained as the profiled piston ascends to top dead center (TDC). From the analysis result, a working model using steel material was developed. In addition, the research scopes also including the development of auxiliary system such as fueling, cranking, intake and exhaust units. Due to shortage of time, some general tuning and engine cranking test were performed in the final development stage.